Meningkatkan Pengetahuan dan Keterampilan UMKM Melalui Strategi Pemasaran dan Keuangan - Lestari, Henny Setyo; Hermawan, Asep; Y. Agus Bagus Budi N; Rahmadina Ardelia; Yunita Kusumaningrum (Dirkantara Indonesia, 2024)
This community service activity was carried out at the Azalea Sector GDC, Cilodong sub-district, Depok City. The partners of this activity are micro and small businesses. MSME actors generally only keep simple records in the form of income and expenses. There are even those who do not record operating expenses, so that the business is seen to be generating large profits because expenses are not recorded properly. The result is that the records do not reflect the actual financial condition of the business. The problem faced by partners is that there is no training on increasing knowledge and management of SMEs seen from the marketing and financial aspects of their business directly. The solution needed for this problem is the provision of training for MSMEs in terms of managing finances using accounting and financial management. The output of this solution is the partner's ability to easily use accounting to improve the financial performance of their business. The output of this solution is in the form of partner knowledge about good and correct business financial management